The Meaning of Moyosingog's Oral Poetry at the Oya' Traditional Ceremony of the Bolaang Mongondow Tribe - Dewi Safitri Labuang; Ellyana Hinta; Zilfa Ahmad Bagtayan (Raja Zulkarnain Education Foundation, 2026)
Moyosingog' oral poetry is a form of oral literature that thrives in the Bolaang Mongondow community, particularly during the oya' traditional ceremony. This oral poetry contains words, phrases, and sentences that represent the cultural values, customs, and social systems of the Bolaang Mongondow community, expressed through meaningful symbols. This research focuses on two issues, namely verbal symbols and nonverbal symbols contained in the Moyosingog' oral poetry in the oya' traditional ceremony of the Bolaang Mongondow Tribe. The purpose of this research is to describe the verbal symbols and nonverbal symbols in the Moyosingog' oral poetry. This research uses a descriptive method with a qualitative approach that aims to reveal the concretization of the meaning of the Moyosingog' oral poetry in the context of the oya' traditional ceremony. The research was conducted in Motabang Village, Bolaang Mongondow Regency, with data collection techniques in the form of observation, interviews, and documentation of the speakers of the Moyosingog' oral poetry and traditional figures involved in the implementation of the ceremony. The results of the study indicate that there are two speakers of the Moyosingog' oral poetry, namely representatives from the female and male parties, and three types of important customs were found mentioned in the oral poetry, namely Guman, Guat, and Gama. The symbols found consist of 18 verbal symbols and 5 nonverbal symbols, each of which has a denotative and connotative meaning. The conclusion of this study shows that the Moyosingog' oral poetry in the oya' traditional ceremony is a tradition of discussing marriage customs and giving oya' customs to the mother of the prospective bride which contains cultural values, social norms, and local wisdom of the Bolaang Mongondow Tribe.